Improved sliding mode power control of doubly-fed-induction generator under wind speed variation - Bouiri Abdesselam; Benoudjafer Cherif; Boughazi Othmane; Abdallah Abden; Chojaa Hamid (Institute of Advanced Engineering and Science, 2021)
Due to drawbacks of classical linear controller like proportional-integral (PI), many studies have been used non-linear controller specially when it comes to robustness, but this is less efficient in sliding mode controller (SM) due to the sign function, this function is known as a problem chattering phenomenon, this main disadvantage it can be compensated by Lyapunov backstepping condition, This paper presents nonlinear power control strategy of the doubly-fed-induction generator (DFIG) for wind application system (WAS) using sliding mode combining with backstepping controller (SM-BS) to control produced statoric powers to mitigate unnecessary chattering effects inherent in traditional SMC, to check the effectiveness of the controller, we compare performance of sliding mode controller and sliding mode controller combining with backstepping (SM-BS) in terms of required reference tracking, robustness under parametric variations of the generator, sensitivity to perturbations and reaction to speed variations under investigating further of the chattering phenomenon.